Options for soil organic carbon maintenance under intensive cropping in the West African savanna - Diels, J.; Lyasse, O.; Sanginga, N.; Vanlauwe, Bernard; Aihou, K.; Iwuafor, E.N.O.; Merckx, Roel; Deckers, J. (2002)
Data from the derived savanna zone in southern Benin indicated that some intensive cropping systems (maize/Cajanus and maize/Mucuna relays; maize/cotton with Senna siamea hedgerows) returned about 12 Mg DM ha-1 year-1 of plant biomass to the soil. This compared favorably with the 8 Mg DM ha-1 year-1 reported for current maize/cotton and maize/cowpea systems. Based on calculations with the Rothamsted carbon model, this extra biomass translates into an increase in the topsoil carbon content of 0.33% C after 20 years. These calculations were found to be in line with available data from long-term experiments in West Africa. While the relation between residue-input rates and soil organic carbon (SOC) buildup is reasonably well known, little is known about how this translates directly into yield benefits. As a way to identify the potential of such benefits, we translated achievable SOC gains into increases in top-soil CEC, pH-buffer capacity, and available water (AW) in the soil profile in relative terms, i.e. relative to the AW without additional SOC buildup, and relative to the CEC and pH-buffer capacity contributed by the mineral soil constituents. This indicated that achievable increases in AW from higher SOC contents are insignificant. Furthermore, we found that increases in CEC and pH-buffer capacity through SOC buildup can be justified only in a limited number of soils where the mineral fraction in the topsoil provides very little buffering. Finally, we used a response-curve approach to single out the various benefits from organic matter inputs and to look at interactions with mineral fertilizers. We also indicated the scope for a more mechanistic interpretation, focusing on the effect of increased pH buffering as a way to minimize losses from NH3 volatilization with urea applications in poorly buffered soils.